THE LINGUOCULTURAL ASPECT OF STUDYING LINGUISTIC PHENOMENA (International journal of artificial intelligence, 2026)
The article examines the issues of the linguocultural approach in studying linguistic phenomena. The relationship between language and culture, the analysis of language in cultural context, and the role of ethnocultural components in linguistics are substantiated. The theoretical and methodological foundations of linguoculturology, the methodology for studying the national-cultural characteristics of language, and the practical significance of linguocultural research are revealed.